Coating film for water electrolysis

The coating film with a catalyst-containing coating on a membrane, featuring a high BET surface area and reduced iridium content, addresses the inefficiencies and cost issues of current catalysts for oxygen evolution reactions in water electrolysis, achieving high activity with lower iridium usage.

JP7660201B2Active Publication Date: 2025-04-10GREENERITY GMBH +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023538771
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-23
Filing Date
2021-12-22
Publication Date
2025-04-10
Estimated Expiration
2041-12-22

AI Technical Summary

Technical Problem

Current catalysts for oxygen evolution reactions in acidic water electrolysis require high iridium content, which is limited and costly, leading to inefficiencies and high costs for large-scale water electrolysis.

Method used

A coating film with a catalyst-containing coating on a membrane, where the catalyst has a maximum BET surface area of 80 m^2/g, contains up to 60% by weight of iridium, and has an iridium content of up to 0.4 mg/cm^2, achieving high activity with low iridium content.

Benefits of technology

The coating film achieves high electrochemical activity for oxygen generation in water electrolysis while significantly reducing the iridium content per unit area, making it more feasible for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660201000004
    Figure 0007660201000004
  • Figure 0007660201000005
    Figure 0007660201000005
  • Figure 0007660201000001
    Figure 0007660201000001
Patent Text Reader

Abstract

The present invention relates to a coated membrane comprising: a membrane having a front surface and a rear surface; a catalyst-containing coating provided on the front surface of the membrane, the catalyst being up to 80 m 2 - an iridium-containing coating provided on the support material and containing iridium oxide, iridium hydroxide or iridium oxide hydroxide or a mixture of at least two of these iridium compounds, the catalyst containing iridium in an amount of up to 60% by weight and the coating provided on the front side of the membrane having a maximum of 0.4 mg iridium / cm 2 The coating film has an iridium content of
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating membrane that can be used as a membrane electrode assembly for water electrolysis.

[0002] Hydrogen is considered to be the energy carrier of the future as it allows for sustainable energy storage, is available for the long term and can also be produced using renewable energy technologies. [Background technology]

[0003] Currently, the most common method for producing hydrogen is steam reforming, in which methane and steam are converted into hydrogen and CO. Water electrolysis constitutes a further variant of hydrogen production, which allows hydrogen to be obtained in high purity.

[0004] There are various methods for water electrolysis, notably alkaline water electrolysis, acidic water electrolysis using polymer electrolyte membranes ("PEM"; PEM water electrolysis), and high temperature solid oxide electrolysis.

[0005] A water electrolysis cell contains a half-cell with an electrode where the oxygen evolution reaction (OER) takes place and a further half-cell with an electrode where the hydrogen evolution reaction (HER) takes place. The electrode where the oxygen evolution reaction takes place is called the anode.

[0006] Overviews of the technology of water electrolysis, particularly PEM water electrolysis, can be found, for example, in M. Carmo et al., International Journal of Hydrogen Energy, 38, 2013, pp. 4901-4934; and V. Himabindu et al., Materials Science for Energy Technologies, 2, 2019, pp. 442-454.

[0007] In a polymer electrolyte membrane water electrolysis cell (hereinafter also referred to as a PEM water electrolysis cell), a polymer membrane serves as a proton transport medium and electrically insulates the electrodes from each other. Catalyst compositions for the oxygen evolution reaction and the hydrogen evolution reaction are applied, for example, as an anode and a cathode on the front and rear surfaces of the membrane ("Catalyst-Coated Membrane, CCM"), thereby obtaining a membrane electrode assembly ("MEA").

[0008] The oxygen evolution reaction occurring at the anode of a PEM water electrolysis cell can be described by the following reaction equation: 2H2O→4H + +O2+4e -

[0009] Due to its complex reaction mechanism, the oxygen evolution reaction is slow and therefore requires significant overpotentials at the anode to achieve sufficiently high conversion rates. Furthermore, the oxygen evolution reaction proceeds under very acidic conditions (i.e., low pH).

[0010] Efficient operation of a water electrolysis cell requires the presence of a catalyst. Since the oxygen evolution reaction at the anode proceeds under highly corrosive conditions (low pH, significant overpotential), especially noble metals such as ruthenium and iridium, as well as their oxides, can be used as suitable catalytic materials.

[0011] Catalytically active metals or metal oxides may optionally be provided on the support material to increase the specific surface area of ​​the catalytic material.

[0012] Regarding the support material, only those materials that have sufficiently high stability under the highly corrosive conditions of the oxygen evolution reaction, for example, transition metal oxides such as TiO2 or oxides of certain main group elements such as Al2O3, can be used. However, many of these oxide support materials are non-conductive, which adversely affects the efficiency of the oxygen evolution reaction and, therefore, water electrolysis.

[0013] A review of catalysts for the oxygen evolution reaction under acidic conditions (i.e. at the anode of a PEM water electrolysis cell) can be found, for example, in P. Strasser et al., Adv. Energy Mater., 7, 2017, 1601275; and FM Sapountzi et al., Progress in Energy and Combustion Science, 58, 2017, pp. 1-35. WO 2005 / 049199(A1) describes catalyst compositions for the oxygen evolution reaction in PEM water electrolysis.

[0014] The catalyst contains iridium oxide and an inorganic oxide which acts as a support material. 2 / g~400m 2 / g and is present in the composition in an amount of less than 20 wt.%. Thus, the catalyst composition has a high iridium content.

[0015] Iridium reserves are very limited. In the publications by M. Bernt et al., "Analysis of Voltage Losses in PEM Water Electrolyzers with Low Platinum Group Metal Loadings", J. Electrochem. Soc. 165, 2018, F305-F314, and M. Bernt et al., "Current Challenges in Catalyst Development for PEM Water Electrolyzers", Chem. Ing. Tech., 2020, 92, no. 1-2, pp. 31-39, it is stated that the current typical iridium loading level on the anode side of catalyst coated membranes is about 1 cm of the coated membrane surface. 2 It has been stated that the iridium content per unit area is approximately 2 mg of iridium per cm of anode electrode surface area, but that this level must still be significantly reduced to allow large-scale use of PEM electrolysis based on the amount of iridium available. 2 It is stipulated to contain 0.05mg of iridium per unit.

[0016] M. Bernt et al., J. Electrochem. Soc. 165, 2018, F305-F314, describe the production of catalyst coated membranes using a commercial catalyst composition containing IrO2 supported on TiO2. The catalyst composition contains iridium (in the form of IrO2) in an amount of 75% by weight. In order to obtain anodes with the lowest possible iridium content levels per unit area, the layer thickness of the anode was reduced. Iridium 0.20-5.41 mg / cm 2 Iridium loading levels per unit area ranging from 1 to 2 mg / cm2 were achieved and tested for their efficiency in water electrolysis. 2 Although good results were obtained at a concentration level of 0.5 mg / cm 2 At loading levels below 0.5 mg / cm of iridium, the anode layer thickness was thin and the resulting electrode layer was non-uniform, significantly impairing the efficiency of water electrolysis. Therefore, this publication proposes modifying the structure or morphology of the catalyst to lower the iridium packing density in the anode; thus, 2 Low iridium inclusion levels of less than 1000 nm can be achieved with the same anode layer thickness (eg, 4-8 μm).

[0017] In M. Bernt et al., Chem. Ing. Tech., 2020, 92, no. 1-2, pp. 31-39, it is stated that a possible approach to reduce the iridium loading density in the anode is to use a support material with a high specific surface area (i.e. a high BET surface area) and to disperse the catalytically active metal iridium or iridium oxide as finely as possible on this support material. In this connection, it is stated in this publication that many of the usual support materials with sufficiently high stability, such as TiO2, are non-conductive and therefore a relatively large amount of Ir or IrO2 (more than 40 wt.%) is required in the catalyst in order to generate a network of Ir or IrO2 nanoparticles as cohesive as possible on the surface of the non-conductive support material. The publication also states that iridium oxide can be dispersed in nanoparticle form on a conductive support material, such as antimony-doped tin oxide, as a possible solution approach.

[0018] European Patent No. 2608297(A1) describes a catalyst for water electrolysis that contains an inorganic oxide acting as a support material and iridium oxide dispersed on the support material. The oxide support material is contained in the catalyst in an amount of 25 to 70% by weight and has a thickness of 30 to 200 μm. 2 / g range of BET surface area.

[0019] C. Van Pham et al., Applied Catalysis B: Environmental, 269, 2020, 118762, describes a catalyst for the oxygen evolution reaction in water electrolysis, which has a core-shell structure in which TiO2 forms the core and IrO2 forms the shell. The core-shell catalyst particles contain 50% by weight of IrO2. The average crystallite diameter of the IrO2 shell is determined to be 10 nm by X-ray diffraction and the Scherrer formula. The anode contains 1.2 mg / cm of iridium. 2 or Iridium 0.4mg / cm 2 Catalyst coated membranes are produced having iridium loading levels per unit area of ​​0.1 to 0.5 μm.

[0020] EP 2608298 A1 describes a catalyst that contains (i) a support material having a core-shell structure and (ii) metal nanoparticles dispersed on the core-shell support, for use in a fuel cell. Summary of the Invention [Problem to be solved by the invention]

[0021] The object of the present invention is to provide a coated membrane that can be used as a membrane electrode assembly in acid water electrolysis, which allows the most efficient possible oxygen evolution reaction on the coating that acts as the anode in the water electrolysis process, in particular this coating should allow high activity at low iridium contents. [Means for solving the problem]

[0022] The object is to provide a coating film, - a membrane having a front surface and a rear surface; - a catalyst-containing coating provided on the front surface of the membrane, The catalyst is - Up to 80m 2 / g of a BET surface area; - an iridium-containing coating provided on a support material and containing iridium oxide, iridium hydroxide or iridium oxide hydroxide, or a mixture of at least two of these iridium compounds, The catalyst contains iridium in an amount of up to 60% by weight, The catalyst-containing coating on the front surface of the membrane is up to 0.4 mg / cm of iridium. 2 This is achieved by a coating film having an iridium content of DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The above properties of the catalyst (i.e., up to 80 m of the support material) 2 / g BET surface area and up to 60 wt. % iridium content) and a very low iridium content in the catalyst-containing coating on the front side of the membrane (up to 0.4 mg iridium / cm of membrane). 2 ), this coating functions as a highly efficient anode with high activity at low iridium content in water electrolysis.

[0024] The catalyst-containing coating provided on the membrane front surface is hereinafter also referred to as the membrane coating, whereas the iridium-containing coating provided on the support material is hereinafter also referred to as the support material coating.

[0025] As known to those skilled in the art, the value of the iridium content of the membrane coating is calculated by dividing the mass ([mg]) of iridium contained in the membrane coating by the area ([cm 2 ])

[0026] The film coverage is preferably up to 0.3 mg iridium / cm 2 , more preferably 0.20 mg / cm of iridium 2 For example, the iridium content of the film coating is 0.01 to 0.4 mg / cm of iridium. 2 , more preferably 0.02 to 0.3 mg / cm of iridium 2 , and even more preferably 0.03 to 0.20 mg / cm of iridium 2 The range is less than.

[0027] The membrane coating has a thickness in the range of, for example, 2 μm to 10 μm, more preferably 3 μm to 8 μm, and even more preferably 3 μm to 7 μm.

[0028] Preferably, the membrane coating (and thus the catalyst) does not contain any metallic iridium (i.e., iridium in the oxidation state 0). The iridium in the membrane coating is preferably present only as iridium in the oxidation state +3 (iridium(III)) and / or iridium in the oxidation state +4 (iridium(IV)). The oxidation state of iridium, and thus the absence of iridium(0) and the presence of iridium(III) and / or iridium(IV), can be confirmed by XPS (X-ray photoelectron spectroscopy). It is further preferred that the iridium in the membrane coating is present only as an iridium-containing coating on a support material.

[0029] The catalyst preferably contains iridium in an amount of up to 40% by weight, more preferably up to 35% by weight, for example, the catalyst contains iridium in an amount of 5% to 60% by weight, more preferably 5% to 40% by weight, even more preferably 5% to 35% by weight.

[0030] Typically the support material (and therefore the catalyst) is in particulate form.

[0031] The carrier material is preferably up to 65 m 2 / g, more preferably up to 50m 2 For example, the BET surface area of ​​the support material is 2 to 80 m 2 / g, more preferably 2 to 65m 2 / g, and even more preferably 2 to 50 m 2 In a preferred embodiment, the BET surface area of ​​the support material is in the range of 2 m 2 / g~40m 2 / g, more preferably 2m 2 / g~10m 2 / g, and even more preferably less than 2m 2 / g~9m 2 / g.

[0032] It may be advantageous for the efficiency of the catalyst with respect to the oxygen evolution reaction if the iridium-containing coating provided on the particulate support material has an average layer thickness in the range of 1.0 nm to 5.0 nm, more preferably 1.5 nm to 4.0 nm, even more preferably 1.7 nm to 3.5 nm. The layer thickness can be adjusted by the amount of iridium oxide, iridium hydroxide or iridium oxide hydroxide deposited on the support material and the BET surface area of ​​the support material. For a given amount of iridium oxide, iridium hydroxide or iridium oxide hydroxide deposited, the larger the BET surface area of ​​the support material, the smaller the layer thickness of the iridium-containing support material coating. The average thickness of the iridium-containing coating provided on the support material is determined by transmission electron microscopy (TEM). The iridium-containing coating on the support material preferably has a relatively uniform layer thickness. For example, the local variation in the average layer thickness is at most two-fold. The relative standard deviation from the average layer thickness is preferably at most 35%. As is commonly known, the relative standard deviation StAbw, which is also called the coefficient of variation, rel (%) is obtained from the following relationship: StAbw rel = [StAbw / MW] x 100 During the ceremony, MW is the average value of the measured variable, i.e. in the present case the average layer thickness (nm); StAbw is the standard deviation from the average layer thickness (nm).

[0033] The catalyst preferably has a core-shell structure, with the support material forming the core and the iridium-containing coating forming the shell. Preferably, the core is completely surrounded by the shell.

[0034] In an exemplary embodiment, the support material is 2 to 65 m 2 / g, the catalyst contains 5 wt% to 40 wt% iridium, and the iridium loading level of the catalyst-containing coating provided on the membrane is between 0.02 and 0.3 mg iridium / cm 2In this preferred embodiment, the average thickness of the iridium-containing support material coating is, for example, in the range of 1.5 nm to 4.0 nm, more preferably 1.7 nm to 3.5 nm.

[0035] In a further exemplary embodiment, the carrier material has a thickness of 2 to 35 μm. 2 / g, the catalyst contains 5 wt% to 35 wt% iridium, and the iridium loading level of the catalyst-containing coating provided on the membrane is between 0.03 and 0.20 mg iridium / cm 2 In this preferred embodiment, the thickness of the iridium-containing support material coating is, for example, in the range of 1.5 nm to 4.0 nm, more preferably 1.7 nm to 3.5 nm.

[0036] In a further exemplary embodiment, the carrier material is 2 / g~10m 2 / g, more preferably less than 2m 2 / g~9m 2 / g, the catalyst contains 5 wt% to 20 wt%, more preferably 5 wt% to 14 wt% iridium, and the iridium loading level of the catalyst-containing coating provided on the membrane is between 0.03 and 0.20 mg iridium / cm 2 In this preferred embodiment, the thickness of the iridium-containing support material coating is, for example, in the range of 1.5 nm to 4.0 nm, more preferably 1.7 nm to 3.5 nm.

[0037] It may be advantageous for the efficiency of the catalyst with respect to the oxygen evolution reaction if the iridium content of the catalyst satisfies the following conditions: (1.003(g / m 2 )×BET) / (1+0.0117(g / m 2 )×BET)≦Ir-G≦(5.015(g / m 2 )×BET / (1+0.0585(g / m 2 )×BET) During the ceremony, BET is the BET surface area (m 2 / g), Ir-G is the iridium content of the catalyst (wt %).

[0038] For example, 10m 2 When a support material having a BET surface area of ​​100-1500 nm / g is used, the above conditions lead to the selection of an iridium content in the range of 9-32 wt. % for the catalyst.

[0039] In a preferred embodiment, the iridium content of the catalyst satisfies the following conditions: (1.705(g / m 2 )×BET) / (1+0.0199(g / m 2 )×BET)≦Ir-G≦(3.511(g / m 2 )×BET) / (1+0.0410(g / m 2 )×BET) During the ceremony, BET is the BET surface area (m 2 / g), Ir-G is the iridium content of the catalyst (wt %).

[0040] Even more preferably, the iridium content of the catalyst satisfies the following conditions: (1.805(g / m 2 )×BET) / (1+0.0211(g / m 2 )×BET)≦Ir-G≦(3.009(g / m 2 )×BET) / (1+0.0351(g / m 2 )×BET) During the ceremony, BET is the BET surface area (m 2 / g), Ir-G is the iridium content of the catalyst (wt %).

[0041] The iridium-containing coating provided on the support material preferably contains iridium oxide hydroxide, which contains hydroxide anions in addition to oxide anions and can be described, for example, by the following formula: IrO(OH)x (1≦x<2).

[0042] For example, the atomic ratio of iridium (IV) to iridium (III) in the iridium-containing coating provided on the support material is at most 4.7 / 1.0, as determined by X-ray photoelectron spectroscopy (XPS). For example, the atomic ratio of iridium (IV) / iridium (III) in the iridium-containing layer on the support material is in the range of 1.0 / 1.0 to 4.7 / 1.0. This can further improve the electrochemical activity of the catalyst. To achieve an advantageous compromise between high electrochemical activity and high electrical conductivity, it may be preferred that the atomic ratio of iridium (IV) / iridium (III) in the iridium-containing layer provided on the support material is in the range of 1.9 / 1.0 to 4.7 / 1.0, more preferably 2.5 / 1.0 to 4.7 / 1.0. The atomic ratio of iridium (IV) / iridium (III) can be adjusted by the temperature of the heat treatment of the catalyst. Heat treatment of the catalyst at high temperatures is advantageous in order to obtain a high iridium(IV) / iridium(III) ratio. Preferred temperatures for the heat treatment of the catalyst are also specified below.

[0043] An advantageous compromise between a sufficiently high electrical conductivity and a high electrochemical activity of the catalyst can be achieved, for example, if the catalyst undergoes a heat treatment during production at a temperature higher than 250°C, for example from 250°C to 550°C, more preferably from 300°C to 450°C, even more preferably from 300°C to 380°C. The heat treatment can be carried out, for example, in an oxygen-containing atmosphere. The heat treatment is carried out, for example, for a period of at least 1 hour, but preferably not more than 3 hours. As a result of this heat treatment (preferably at 300°C to 450°C, more preferably at 300°C to 380°C), the electrical conductivity of the catalyst can be significantly increased (for example, 50 to 100 times) compared to a catalyst that has not been heat treated, while the electrochemical activity is only slightly reduced (for example, 1.5 to 2 times).

[0044] The catalyst preferably does not contain metallic noble metals (such as platinum, palladium, iridium, rhodium, ruthenium, osmium, silver or gold). By metallic noble metal is meant a noble metal in the oxidation state 0. The absence of metallic noble metals can be confirmed by XPS.

[0045] Optionally, the iridium-containing coating provided on the support material may still contain ruthenium in the oxidation state +3 (Ru(III)) and / or the oxidation state +4 (Ru(IV)).

[0046] Suitable support materials onto which the iridium-containing coating can be deposited are known to those skilled in the art. For example, the support material is an oxide of a transition metal (e.g. titanium oxide (e.g. TiO2), zirconium oxide (e.g. ZrO2), niobium oxide (e.g. Nb2O5), tantalum oxide (e.g. Ta2O5) or cerium oxide), an oxide of a main group metal (e.g. aluminum oxide such as Al2O3), SiO2, or a mixture of two or more of the aforementioned support materials. In a preferred embodiment, the support material is titanium oxide.

[0047] The catalyst is preferably prepared by a wet chemical process in which iridium oxide, iridium hydroxide or iridium oxide hydroxide is deposited on a particulate support material under alkaline conditions and, optionally, by thermal post-treatment.

[0048] Alternatively, the iridium-containing coating can be deposited on the support material by spray pyrolysis.

[0049] For example, the catalyst may be - depositing an iridium-containing solid on a support material in an aqueous medium containing an iridium compound at a pH of ≥ 9; - separating the support material carrying the iridium-containing solid from the aqueous medium and optionally carrying out a heat treatment.

[0050] The carrier material to be coated is provided in a dispersed form in an aqueous medium. The aqueous medium contains an iridium compound that can be precipitated as an iridium-containing solid under alkaline conditions. Such iridium compounds are known to those skilled in the art. The iridium compound is preferably an iridium(IV) or iridium(III) compound.

[0051] As already mentioned above, the layer thickness of the support material coating can be adjusted by the amount of iridium oxide, iridium hydroxide or iridium oxide hydroxide deposited on the support material and the BET surface area of ​​the support material. For a given amount of iridium oxide, iridium hydroxide or iridium oxide hydroxide applied, the larger the BET surface area of ​​the support material, the smaller the layer thickness of the iridium-containing coating on the support material.

[0052] Suitable iridium(III) or iridium(IV) compounds that precipitate as solids under alkaline conditions in aqueous solution are known to those skilled in the art. For example, iridium(III) or iridium(IV) compounds may be salts (e.g., iridium halides such as IrCl3 or IrCl4; iridium halides such as IrCl6, where the anion is a chloro complex; 2- iridium nitrate or iridium acetate), or an iridium-containing acid, such as H2IrCl6. In a preferred embodiment, the aqueous medium contains an iridium(IV) halide, in particular Ir(IV) chloride.

[0053] Optionally, ruthenium (III) and / or ruthenium (IV) compounds may also be included in the aqueous medium. This allows deposition of iridium-ruthenium hydroxide oxide on the support material. When a ruthenium precursor compound is included in the aqueous medium, the compound may be, for example, a Ru(III) or Ru(IV) salt, such as a halide, nitrate or acetate.

[0054] Preferably, the aqueous medium for depositing the iridium-containing solid on the support material has a pH of at least 10, more preferably at least 11. For example, the aqueous medium has a pH of 9-14, more preferably 10-14 or 11-14.

[0055] The aqueous medium typically contains at least 50% by volume water, more preferably at least 70% by volume, and even more preferably at least 90% by volume water.

[0056] The temperature of the aqueous medium for depositing the iridium-containing solid on the support material is, for example, 40°C to 100°C, more preferably 60°C to 80°C.

[0057] The support material can, for example, be dispersed in an aqueous medium that already contains one or more iridium(III) and / or iridium(IV) compounds, but has a pH (for example at room temperature) of less than 9. The pH of the aqueous medium is then increased to a value of 9 or more by adding a base, and optionally the temperature of the aqueous medium is also increased, until an iridium-containing solid is deposited on the support material by a precipitation reaction. Alternatively, it is also possible, for example, to disperse the support material in an aqueous medium that does not yet contain iridium compounds, and to add the iridium(III) and / or iridium(IV) compounds to the aqueous medium only after the appropriate pH and, optionally, a certain precipitation temperature have been set.

[0058] If ruthenium(III) and / or ruthenium(IV) compounds are also contained in the aqueous medium, the solid deposited on the support material by precipitation contains ruthenium in addition to iridium. The atomic ratio of iridium to ruthenium may, for example, be in the range of 90 / 10 to 10 / 90.

[0059] Separation of the support material carrying the iridium-containing solid from the aqueous medium is accomplished by methods known to those skilled in the art (eg, by filtration).

[0060] The support material carrying the iridium-containing solid is dried. The dried iridium-containing solid provided on the support material is, for example, iridium oxide hydroxide. The iridium oxide hydroxide contains hydroxide anions in addition to oxide anions and can be described, for example, by the following formula: IrO(OH)x (1≦x<2).

[0061] As already explained above, if the thermal post-treatment is carried out at a slightly higher temperature, the electrical conductivity of the iridium-containing coating provided on the support material and thus of the catalyst can be improved. An advantageous compromise between a sufficiently high electrical conductivity and a high electrochemical activity of the catalyst can be achieved, for example, when the coated support material is subjected to a heat treatment at a temperature higher than 250°C, for example from 250°C to 550°C, more preferably from 300°C to 450°C, even more preferably from 300°C to 380°C. The heat treatment can be carried out, for example, in an oxygen-containing atmosphere. The heat treatment is carried out, for example, for a period of at least 1 hour, but preferably not more than 3 hours.

[0062] The coating provided on the membrane preferably contains an ionomer in addition to the catalyst. Suitable ionomers are known to those skilled in the art. For example, the ionomer is a polymer containing a sulfonic acid group-containing monomer; in particular, a copolymer containing tetrafluoroethylene and a sulfonic acid group-containing fluorovinyl ether as monomers. The coating provided on the membrane contains the ionomer in an amount of, for example, 2% by weight to 20% by weight.

[0063] Suitable membranes that can be used for PEM water electrolysis are known to those skilled in the art. For example, the membrane contains a polymer that contains a monomer containing sulfonic acid groups; in particular, a copolymer that contains tetrafluoroethylene and a fluorovinyl ether containing sulfonic acid groups as monomers. An overview of polymers suitable for membranes can be found, for example, in the following publications: A. Kusoglu and AZ Weber in Chem.Rev.,2017,117,pp.987-1104.

[0064] The catalyst-containing membrane coating can be applied to the membrane by conventional methods known to those skilled in the art.For example, the ink containing the catalyst composition and optionally an ionomer can be directly applied to the membrane, and after suitable drying, a coated membrane can be obtained.Alternatively, in a method known as the decal method, the catalyst-containing coating can be first applied to a support film or decal film, and then transferred from the decal film to the membrane by pressure and sufficiently high temperature.

[0065] When the coated membrane is used as a membrane electrode assembly in a water electrolysis cell, the catalyst-containing coating on the front side of the membrane acts as the anode where the oxygen evolution reaction takes place.

[0066] A coating containing a catalyst for the hydrogen evolution reaction (HER catalyst) can be deposited on the rear surface of the membrane. Suitable HER catalysts (e.g., catalysts containing a support material and a noble metal deposited thereon) are known to those skilled in the art.

[0067] The present invention further relates to a water electrolysis cell containing the above-described coated membrane.

[0068] Measurement method In connection with the present invention, the following measurement methods were used:

[0069] Average thickness of the iridium-containing support material coating The average thickness of the iridium-containing coating on the support material was determined by TEM (Transmission Electron Microscopy) The average thickness is obtained from the arithmetic mean of the layer thicknesses of the iridium-containing coating determined at at least 10 different points in at least two TEM images.

[0070] A few μg of the material to be investigated were suspended in ethanol. A drop of the suspension was then pipetted onto a carbon perforated film-coated Cu platelet (Plano, 200 mesh) and allowed to dry. The layer thickness measurements were performed at a magnification of 500,000 times. By carrying out parallel EDX elemental analysis of the elements (e.g. Ti) and Ir contained in the support material, it is possible to see in the TEM images which regions on the support material particles contain iridium.

[0071] The thickness of the iridium-containing coating was determined on at least two TEM images, in each case at least five points on the TEM image. Each TEM image shows several grains. The arithmetic mean of these layer thicknesses gave the average thickness of the iridium-containing coating.

[0072] The relative standard deviation from the average layer thickness, StAbw, also called the coefficient of variation rel (%) is obtained in a known manner from the following relationship: StAbw rel = [StAbw / MW] x 100 During the ceremony, MW is the average layer thickness (nm); StAbw is the standard deviation from the average layer thickness (nm).

[0073] The (absolute) standard deviation (nm) is obtained in a known manner via the square root of the variance.

[0074] Iridium Content The iridium content, and, if present, the ruthenium content, are determined by optical emission spectrometry with inductively coupled plasma (ICP-OES).

[0075] BET surface area The BET surface area was determined according to the BET theory (multipoint method, ISO 9277:2010) at 77 K using nitrogen as the adsorbate.

[0076] Atomic ratio of Ir(IV) to Ir(III) The relative ratio of Ir atoms in oxidation state +4 to Ir atoms in oxidation state +3, and thus the Ir(IV) / Ir(III) atomic ratio in the supported iridium hydroxide oxide, was determined by X-ray photoelectron spectroscopy (XPS). This ratio is determined in the detailed spectrum of the Ir(4f) doublet (BE 75-55 eV, Al-kα source) by asymmetric PeakFit-Shirley background, Gaussian-Lorentzian mixing with a Gaussian ratio of 30% and a tailoring factor of 0.7. Furthermore, the presence of IrOH species in the O(1s) detailed spectrum (BE about 531 eV, Al-kα source) is similarly detected by asymmetric PeakFit (Shirley background, Gaussian-Lorentzian mixing with a Gaussian ratio of 30%). The corresponding procedure is described, for example, in Abbott et al., Chem. Mater, 2016, 6591-6604.

[0077] It is also possible to ascertain whether iridium(0) is present in the composition by XPS analysis.

[0078] Thickness of the catalyst-containing membrane coating The thickness of the catalyst-containing membrane coating was determined by examining the cross-section of the catalyst-coated membrane with a scanning electron microscope. SEM analysis was performed at an accelerating voltage of 5-15 kV.

[0079] The present invention will now be described in more detail with reference to the following examples. EXAMPLES

[0080] Preparation of the catalyst used in the examples Catalyst 1 (“Cat-1”) 124.56 g of iridium(IV) chloride (IrCl4 hydrate, Heraeus Deutschland GmbH & Co. KG) was dissolved in 4000 mL of water at room temperature. Then, 60.17 g of TiO2 (P25, Evonik, BET surface area: 60 m 21000g / g of iridium-containing solid was added. The pH was adjusted to 9.7 by adding NaOH. The aqueous medium was heated to 70° C. and the pH was adjusted to 11. The mixture was stirred at 70° C. overnight. The pH was maintained at 11. The TiO2 support material loaded with iridium-containing solid was filtered off, washed and dried. A thermal post-treatment was performed at 350° C. for 1 h in an oxygen-containing atmosphere. XPS analysis showed that the dried iridium-containing solid provided on the support was iridium oxide hydroxide.

[0081] Catalyst 2 (“Cat-2”) 27.80 g of iridium(IV) chloride (IrCl4 hydrate, Heraeus Deutschland GmbH & Co. KG) was dissolved in 4000 mL of water at room temperature. Then, 29.94 g of TiO2 (DT20, Tronox, BET surface area: 20 m 2 1000g) was added. The pH was adjusted to 10.3 by adding NaOH. The aqueous medium was heated to 70°C and the pH was adjusted to 11 as before. The mixture was stirred at 70°C overnight. The pH was maintained above 11.0. The TiO2 support material loaded with iridium-containing solid was filtered off, washed and dried. A thermal post-treatment was performed at 350°C for 1 hour in an oxygen-containing atmosphere. XPS analysis showed that the dried iridium-containing solid provided on the support was iridium oxide hydroxide.

[0082] Catalyst 3 (“Cat-3”) A commercially available catalyst was used, which contains IrO2-coated TiO2 as the support material.

[0083] Catalyst 4 (“Cat-4”) 48.35 g of iridium(IV) chloride (IrCl4 hydrate, Heraeus Deutschland GmbH & Co. KG) was dissolved in 4000 mL of water at room temperature. Then, 51.9 g of TiO2 (Active G5, Tronox, BET surface area: 150 m 21000g / g of iridium-containing solid was added. The pH was adjusted to 11.2 by adding NaOH. The aqueous medium was heated to 70°C and the pH was adjusted to >9.0. The mixture was stirred at 70°C overnight. The pH was maintained >9.0. The TiO2 support material loaded with iridium-containing solid was filtered off, washed and dried. A thermal post-treatment was performed at 350°C for 1 hour in an oxygen-containing atmosphere. XPS analysis showed that the dried iridium-containing solid provided on the support was iridium oxide hydroxide.

[0084] The iridium content of the catalysts and the BET surface areas of the support materials are summarized in Table 1 below.

[0085] [Table 1]

[0086] Preparation of coating film and activity measurement Each of the catalysts Cat-1 to Cat-4 was dispersed in a liquid phase together with a fluorinated ionomer. The same ionomer and the same solvent were used in all the dispersions prepared.

[0087] Each dispersion was applied to a transfer film (decal film). After drying at 110°C for 5 minutes, the material was transferred from the transfer film to a membrane (Nafion® NR212, Chemours, USA). The transfer was performed at a temperature of 170°C and a pressure of 1.5 MPa (time: 1 minute). The material containing one of the catalysts Cat-1 to Cat-4 transferred to the membrane served as the anode.

[0088] Additionally, a cathode was attached to the membrane by a decal method. The cathode was the same in all examples and contained platinum supported on carbon and a fluorinated ionomer.

[0089] The anode, membrane and cathode together form a membrane electrode assembly ("catalyst coated membrane" CCM). In Examples EB1 to EB3 according to the invention and Comparative Examples VB1 to VB3, described in more detail below, these membrane electrode assemblies differ only in the anode.

[0090] In the first series of tests (Example EB1 according to the invention and Comparative Example VB1), 2 The efficiency of the CCM was measured in a single cell with an active surface area of ​​1000 nm. The cell consisted of a platinized titanium plate with rod-shaped channels ("column bar flow field" design) on the anode and cathode sides. Uncoated sintered titanium bodies (1 mm thick) were used for the porous transport layers on both the anode and cathode sides. Catalysts Cat-2 (example EB1 according to the invention) and Cat-4 (comparative example VB1 1) were used in this series of tests.

[0091] In the second series of tests (Examples EB2 to EB3 according to the invention and Comparative Examples VB2 to VB3), 2 The efficiency of the CCM was measured in a single cell with an active surface area of ​​1000 nm. The cell consisted of a gold-plated titanium plate with serpentine channels ("single serpentine flow field" design) on the anode and cathode sides. In both cases, a gold-coated titanium sintered body was used as a porous transport layer on the anode side. In this series of tests, catalysts Cat-1 (example EB2 according to the invention), Cat-2 (example EB3 according to the invention, comparative example VB3) and Cat-3 (comparative example VB2) were used.

[0092] In all series of tests, carbon paper (Toray TGP-H-120) was used on the cathode side as a gas diffusion layer. Deionized water with a conductivity of less than 1 μS / cm was circulated on the anode side. The cell was heated from room temperature to 60 °C within 20 min. The temperature was then increased to 80 °C within 20 min.

[0093] In the first series of tests (EB1, VB1), 1A / cm2 The current density was held at 0 A / cm for 1 h, then reduced to 0 A / cm with a hold time of 5 min for each step. 2 and 1A / cm 2 Conditioning was performed by cycling 10 times between 1 A / cm 2 The temperature was maintained at 80°C, 65°C, and 50°C for 10 minutes. In each case, the current density was increased from a small value to a large value (A / cm2) with a holding time of 10 minutes. 2 The current-voltage characteristics (polarization curve) were recorded by increasing the voltage to 10 V. The details of the steps were as follows: 0.01-0.02-0.03-0.05-0.08-0.1-0.2-0.4-0.6-0.8-1.0-1.2-1.4-1.6-1.8-2.0-2.25-2.5-2.75-3.0 (all in A / cm 2 ).

[0094] In the second series of tests (EB2-EB3, VB2-VB3), the 2 Conditioning was performed by holding the current density at 80°C for 30 min. The current density was increased from low to high (A / cm2) with a holding time of 5 min in each case. 2 The current-voltage characteristics (polarization curve) were recorded by increasing the voltage to 10 V. The details of the steps were as follows: 0.01-0.02-0.03-0.05-0.1-0.2-0.3-0.6-1.0-1.5-2.0-2.5-3.0-3.5-4.0-4.5-5.0-5.5-6.0 (all in A / cm 2 In this case, the first two current-voltage characteristics are still considered part of the conditioning, and the third current-voltage characteristic is shown as the measured curve in Figure 2.

[0095] The layer thickness, iridium content level and electrochemical activity of the anodes of Examples EB1 and VB1 are summarized in Table 2. For greater clarity, the characteristics of the catalyst contained in the anode are also shown again in Table 2 (see also Table 1 above).

[0096] FIG. 1 shows the measurement curves of the membrane electrode assemblies of Examples EB1 and VB1.

[0097] [Table 2]

[0098] In both EB1 and VB1, the iridium content of the anode was 0.4 mg iridium / cm 2 However, in VB1, the support material of the catalyst contained in the anode was 80 m 2 The membrane electrode assembly of Example EB1 according to the present invention (the BET surface area of ​​the support material was 80 m 2 / g) surprisingly had significantly higher electrochemical activity compared to Comparative Example VB1.

[0099] The layer thickness, iridium content level and electrochemical activity of the anodes of Examples EB2-EB3 and VB2-VB3 are summarized in Table 3. For greater clarity, the characteristics of the catalysts contained in the anodes are also shown again in Table 3 (see also Table 1 above).

[0100] FIG. 2 shows the measurement curves of the membrane electrode assemblies of Examples EB2 to EB3 and VB2 to VB3.

[0101] [Table 3]

[0102] In Example EB3 according to the invention and Comparative Example VB3, the anode contained the same catalyst (iridium content of the catalyst: 30% by weight; BET surface area of ​​the support material: 20 m 2 / g). However, the anode of Comparative Example VB3 contained 0.4 mg / cm 2 The membrane electrode assembly of Example EB3 according to the present invention (the iridium content of the anode was 0.4 mg Ir / cm 2(less than 0.01%) surprisingly exhibited significantly higher electrochemical activity compared to Comparative Example VB3.

[0103] This result indicates that the coating film according to the present invention exhibits extremely high activity in the oxygen evolution reaction in water electrolysis. [Brief description of the drawings]

[0104] Not specified.

Claims

1. A coating film, a membrane having a front surface and a rear surface, a catalyst-containing coating provided on the front surface of the membrane and containing a catalyst for the oxygen evolution reaction in water electrolysis; Contains The catalyst is a support material having a BET surface area of ​​between 2 m 2 / g and 80 m 2 / g, - an iridium-containing coating provided on said support material and containing iridium oxide, iridium hydroxide or iridium oxide hydroxide or a mixture of at least two of these iridium compounds; Contains The catalyst contains iridium in an amount of 5% to 60% by weight; The coating provided on the front surface of the membrane has an iridium content of 0.01 to 0.4 mg / cm2 of iridium.

2. The iridium content of the coating provided on the front surface of the membrane is up to 0.3 mg iridium / cm 2 The coating film according to claim 1 , 3. The coating film according to claim 1, wherein the iridium content of the coating provided on the front surface of the film is less than 0.20 mg / cm 2 of iridium.

4. The coated membrane according to any one of claims 1 to 3, wherein the catalyst contains iridium in an amount of up to 40% by weight.

5. The coating film of claim 1, wherein the catalyst contains iridium in an amount of up to 35% by weight.

6. The carrier material is up to 65 m 2 The coating according to any one of claims 1 to 5, having a BET surface area of ​​1 / g.

7. The coating membrane of claim 1, wherein the support material has a BET surface area of ​​up to 50 m 2 / g.

8. The coating membrane of claim 1, wherein the support material has a BET surface area in the range of 2 m 2 / g to 40 m 2 / g.

9. The coating according to any one of claims 1 to 8, wherein the iridium-containing coating provided on the support material has an average layer thickness in the range of 1.0 nm to 5.0 nm.

10. The coating film according to claim 1, wherein the iridium-containing coating provided on the carrier material has an average layer thickness in the range of 1.5 nm to 4.0 nm.

11. The coating film according to claim 1, wherein the iridium-containing coating provided on the carrier material has an average layer thickness in the range of 1.7 nm to 3.5 nm.

12. The carrier material is 2 to 35 m 2 / g, the catalyst contains 5 wt % to 35 wt % iridium, and the iridium loading level of the catalyst-containing coating on the front surface of the membrane is between 0.03 and 0.20 mg iridium / cm 2 The coating film according to any one of claims 1 to 11, wherein the coating film has a viscosity of less than 1000 MPa.

13. The BET surface area of ​​the support material and the iridium content of the catalyst are such that: (1.003(g / m 2 )×BET) / (1+0.0117(g / m 2 )×BET)≦Ir-G≦(5.015(g / m 2 )×BET / (1+0.0585(g / m 2 )×BET) where BET is the BET surface area (m 2 / g), Ir-G is the iridium content (wt%) of the catalyst. The coating film according to any one of claims 1 to 12, which satisfies the above.

14. The coated membrane of any one of claims 1 to 13, wherein the catalyst has a core-shell structure, in which the support material forms the core and the iridium-containing coating forms the shell.

15. the iridium is present only as iridium in the oxidation state +3 (iridium(III)) and / or iridium in the oxidation state +4 (iridium(IV)); and / or 15. The coating of any one of claims 1 to 14, wherein the iridium-containing coating has an atomic ratio of iridium (IV) to iridium (III) of up to 4.7 / 1.0 as determined by X-ray photoelectron spectroscopy (XPS).

16. The support material is selected from the group consisting of transition metal oxides, main group metal oxides, SiO 2 or a mixture of two or more of the aforementioned carrier materials.

17. A coating according to any one of the preceding claims, wherein the coating provided on the front surface of the membrane has a thickness in the range of 2 μm to 10 μm.

18. The coating film according to claim 1, wherein the coating provided on the front surface of the film has a thickness in the range of 3 μm to 8 μm.

19. The coating film according to claim 1, wherein the coating provided on the front surface of the film has a thickness in the range of 3 μm to 7 μm.

20. The coated membrane according to any one of claims 1 to 19, wherein the coating provided on the membrane front surface contains an ionomer.

21. The coating film of claim 20, wherein the ionomer is a polymer containing a sulfonic acid group-containing monomer.

22. The coated membrane of any one of claims 1 to 21, wherein a coating containing a catalyst for a hydrogen evolution reaction is applied to the rear surface of the membrane.

23. Use of the coated membrane according to any one of claims 1 to 22 as a membrane electrode assembly for water electrolysis.

24. A water electrolysis cell comprising the coating membrane according to any one of claims 1 to 22.

Citation Information

Patent Citations

  • Isothermal dehumidification oxygen-enriched electrochemical device and application

    CN106400047A

  • Anode catalyst for water electrolysis hydrogen production by taking transition metal doped titanium oxide as a carrier and preparation method of anode catalyst

    CN111266110A

  • Precious metal oxide catalyst for water electrolysis

    EP2608297A1

  • Electrocatalyst composition comprising a noble metal oxide supported on tin oxide

    JP2020500692A